1920 : the year that made the decade roar - Burns, Eric (Pegasus Books, 2015)
Acclaimed author Eric Burns investigates the year of 1920, which was not only a crucial twelve-month period of its own, but one that foretold the future, foreshadowing the rest of the 20th century and the early years of the 21st, whether it was Sacco and Vanzetti or the stock market crash that brought this era to a close.